Treatment of industrial wastewater with two-stage constructed wetlands planted with typha latifolia and phragmites australis - Calheiros, Cristina S.C. (2010)
Industrial wastewater treatment comprises several processes to fulfill the discharge permits or to enable the reuse of wastewater. For tannery wastewater, constructed wetlands (CWs) may be an interesting treatment option. Two-stage series of horizontal subsurface flow CWs with Phragmites australis (UP series) and Typha latifolia (UT series) provided high removal of organics from tannery wastewater, up to 88% of biochemical oxygen demand (BOD5) (from an inlet of 420 to 1000 mg L-1) and 92% of chemical oxygen demand (COD) (from an inlet of 808 to 2449 mg L-1), and of other contaminants, such as nitrogen, operating at hydraulic retention times of 2, 5 and 7 days. No significant (P < 0.05) differences in performance were found between both the series. Overall mass removals of up to 1294 kg COD ha-1 d-1 and 529 kg BOD5 h-1 d-1 were achieved for a loading ranging from 242 to 1925 kg COD ha-1 d-1 and from 126 to 900 kg BOD5 ha-1 d-1. Plants were resilient to the conditions imposed, however P. australis exceeded T. latifolia in terms of propagation.